2012
DOI: 10.1177/1098611112447611
|View full text |Cite
|
Sign up to set email alerts
|

What is Known About the Effectiveness of Police Practices in Reducing Crime and Disorder?

Abstract: We build upon previous reviews of the police effectiveness literature to categorize strategies and tactics based on what police should and should not be doing. We also provide relevant information on what police agencies should be doing to implement effective strategies. We argue police should be focusing on hot spots policing, problem-oriented policing (POP), focused deterrence approaches, directed patrol to reduce gun crime, and using DNA in property cases. Police should also recognize the importance of effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 89 publications
(110 reference statements)
2
94
1
2
Order By: Relevance
“…No. A recent study in Sacramento, California demonstrated that random police deployments could be effective at micro-spatial scales (Telep and Weisburd 2012); randomly rotating officers between treatment group street blocks resulted in significant overall reductions in both calls for service and Part 1 crime incidents. Random preventive patrols have been routinely described as an ineffective crime control measure over large areas (Kelling et al 1974;Weisburd and Eck 2004;Telep and Weisburd 2012) but the rotating deployment of officers increases the unpredictability of enforcement at locations whose size encourages expected police behavior.…”
Section: Discussionmentioning
confidence: 99%
“…No. A recent study in Sacramento, California demonstrated that random police deployments could be effective at micro-spatial scales (Telep and Weisburd 2012); randomly rotating officers between treatment group street blocks resulted in significant overall reductions in both calls for service and Part 1 crime incidents. Random preventive patrols have been routinely described as an ineffective crime control measure over large areas (Kelling et al 1974;Weisburd and Eck 2004;Telep and Weisburd 2012) but the rotating deployment of officers increases the unpredictability of enforcement at locations whose size encourages expected police behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Is the CV strategy cost-beneficial? Policy makers and researchers lament the lack of cost-effectiveness research associated with these and other violence reduction strategies, and they stress that the lack thereof hampers expansion and replication of innovative strategies (11). The public health approach pursued by CV is different from that of most violence reduction models.…”
Section: Evaluation Challenges and Limitationsmentioning
confidence: 99%
“…Paying attention to lighting, implementing patrolling security guards, and operating CCTV may help with altering human behavior and ultimately prevent crime (Savard & Kennedy, 2014). However, the effectiveness of lighting may only be good insofar as it prevents specific types of crimes and not crimes in general , whereas the efficacy of patrolling security guards and CCTV regarding their deterrent value have been challenged (Telep & Weisburd, 2012;.…”
Section: From a Practical Standpoint A Related Perspective Associatementioning
confidence: 99%